Need Analysis of a Physics E-Book on Global Warming Based on the Dual Space Inquiry Framework to Improve Students’ Scientific Literacy - Nngsih, Fitria; Novitra, Fuja; Fauzi, Ahmad; Emiliannur, Emiliannur (Universitas Negeri Padang, 2025)
This research is motivated by the low scientific literacy of students as indicated by the PISA 2022 results, as well as the continued dominance of printed teaching materials in schools. This condition limits students’ opportunities to engage in scientific thinking, interpret data, and use scientific evidence effectively. The purpose of this study is to analysis the need for developing an interactive e-book based on the Dual Space Inquiry Framework (DSIF) on the topic of global warming to improve students’ scientific literacy. The study employed a needs analysis approach within the Analysis stage of the ADDIE development model by collecting quantitative data related to scientific literacy indicators and the frequency of teaching material usage. The analysis shows that all scientific literacy indicators fall into the low category with an average score of 70.3%, particularly in the abilities to interpret data and evaluate scientific arguments. The data on teaching material usage also reveal a dominance of printed books at 91%, while digital teaching materials are used by only 37% of students and interactive e-books by merely 12%. These findings not only illustrate the low level of scientific literacy but also highlight an urgent need for more interactive digital learning media. Based on this analysis, the Analysis stage of ADDIE emphasizes the necessity of developing a DSIF-based interactive e-book as an innovative solution that will proceed to the Design and Develop stages to produce teaching materials capable of supporting inquiry, conceptual understanding, and scientific thinking skills.